Post natal expression of Prx1 labels appendicular restricted progenitor cell populations of multiple tissues. Issue 5 (26th March 2022) - Bragdon, Beth C.; Bennie, Andrew; Molinelli, Amanda; Liu, Yu; Gerstenfeld, Louis C.
Abstract: Currently, there is no consensus whether there is a single or multiple postnatal stem cell population(s) that contribute to skeletal homeostasis and postnatal bone formation. A known population of cells that express Prx1 contributes to postnatal bone formation. Prx1 expression also connotes calvaria and appendicular tissues during embryonic development. A transgenic tamoxifen inducible Prx1 reporter mouse was used for lineage tracking, to characterize the postnatal contribution of Prx1 expressing cells in skeletal homeostasis and bone formation. Under homeostatic conditions Prx1 labeling gave rise to a transient yet rapid turnover cell population at the periosteal and endosteal surfaces, along muscle fibers, and within the medial layers of vessels both within the muscle and marrow compartments of the appendicular skeleton. Fracture and ectopic bone formation of both fore and hind limbs showed recruitment and expansion of Prx1‐derived cells in newly formed bone tissues. Prx1 labeled cells were limited or absent at axial skeletal sites during both homeostasis and after induction of bone formation. Last, Prx1‐derived cells differentiated into multiple cell lineages including vascular smooth muscle, adipose, cartilage, and bone cells. These results show that Prx1 expression retained its embryonic tissue specification and connotes a stem/progenitor cell populations of mesenchymal tissue progenitors. Abstract : A transgenic tamoxifen inducible Prx1 reporter mouse was used for lineage tracking, to characterize the post‐natal contribution of Prx1 expressing cells in skeletal homeostasis and bone formation. Under homeostatic conditions Prx1 cells gave rise to a transient yet rapid turnover cell population at multiple tissue sites and greatly contributes to multiple postnatal bone formation models while retaining its embryonic tissue specification. The Prx1 cell population connotes a stem/progenitor cell populations of mesenchymal tissue progenitors.